The efficacy of conservative treatment for late term ovarian torsion - Kazez, A.; Ozel, S. K.; Akpolat, N.; Goksu, M. (Georg Thieme Verlag Kg, 2007)
Background/Purpose: Recent reports have focused on detorsion after ovarian torsion in the literature. The aim of the study was to investigate late term changes in both ovaries after delayed detorsion following ovarian torsion in rats. Materials: Female, prepubertal, Wistar albino rats were divided into four groups (n=6/group). The left ovaries were used for the study and the right ovaries were kept as the control. The groups were constituted as follows: Group 1: left ovarian fixation, bilateral oophorectomy 48 hours later; Group 2: left ovarian torsion and fixation, bilateral oophorectomy 48 hours later; Group 3: detorsion 48 hours after torsion and bilateral oophorectomy after another 48 hours; Group 4: detorsion 48 hours after torsion and bilateral oophorectomy after 21 days. The total injury score (TIS) was compiled histologically in a double-blind fashion. Congestion, edema, bleeding and polymorphonuclear lymphocyte infiltration were assessed for TIS. Results: The TIS was found to be 8 points in Group 1; 38 in Group 2; 28 in Group 3 and 12 in Group 4, respectively. The TIS was based on results from the left ovaries in Group 1, whereas 31 points were attributable to the left ovaries and 7 to the right ovaries in Group 2. In Groups 3 and 4, TIS points were the same in both study and control ovaries. The difference between the left ovaries of Groups 1 and 2 and the left ovaries of Groups 2 and 4 was statistically significant (p < 0.05). Conclusion: Viable ovarian tissue can be detected even after 48 hours of torsion, which is a relatively long period of ischemia. Tissue injury decreases significantly after detorsion during late recovery. In view of previous case reports in the literature and the present findings, detorsion is recommended in children with ovarian torsion regardless of the ischemic period and/or macroscopic appearance.
Keywords: ovarian torsion; detorsion; management; experimental